Tax-Oriented Fair Production Cost Model: A Study in Central Sulawesi and North Maluku - Rondang Pratama Setiawan (Polytechnic of State Finance STAN, 2026)
The nickel industry in Indonesia has been experiencing rapid growth in line with increasing global demand. This growth impacts state revenues, particularly regarding Land and Building Tax (PBB) for the mineral and coal sector (Minerba). However, the government has not established a standardized reference for determining reasonable production costs. This study aims to identify the factors influencing nickel production costs and develop a model for determining the fairness of production costs in the nickel industry. The research employs multiple linear regression to identify significant factors affecting production costs and constructs a production cost model using the stepwise method. The results indicate that production volume has a significant impact on production costs, where each additional ton of production increases production costs by IDR 252,553.7. Meanwhile, other variables such as land area, nickel grade, location, and macroeconomic factors do not significantly influence production costs. The resulting production cost calculation model is as follows: Bp = 3,87 x 10^10 + 252,553.7 x Prod + U This model can serve as a reference for determining the fairness of nickel production costs and support tax policy in calculating PBB Minerba